Agroforestry tourism in India - Scope, opportunities and experiences - Parthiban, K.T.; A, Keerthika (Indian Journal of Agroforestry, 2023)
Tourism has been a part of national economic development due to growing attraction among the people. India is predominantly an agricultural country and over 70% of the population depends on agriculture either directly or indirectly. However, these agriculture land use system has been recognized only for production purposes till the recent past. Agrotourism has gained significant attraction and extend a new dimension to agriculture by judicial integration of agri with tourism industry. However, agroforestry tourism has not been thought of but has created opportunity compared to other land use system due to itsmultifunctionality in extending all ecosystem and environmental services. Though agroforestry is a traditional land use system practiced as a livelihood system but gained attraction as a source of commercial and economic importance only in the recent past. The growing importance of integration of trees in urban, semi-urban, panchayat and other land uses for recreational, aesthetic, cultural and other services have extended a greater scope of treating agroforestry as a tourism destination. The retrieved information from Web of Science (WoS) bibliometric review displays 68 records for the keyword search 'agroforestry tourism' which itself is a evidence that it has been focused relatively less in terms of tourism. Therefore, considering, the growing importance of agroforestry in augmenting productivity, enhancing profitability and its role in cultural, regulation and other supporting services, the current research group has conceived and developed the concept of agroforestry tourism in twolocations and presented with opportunities and challenges in agroforestry tourism.